The Halo’s Ancient Metal-Rich Progenitor Revealed with BHB Stars - Lancaster, Lachlan; Koposov, Sergey E; Belokurov, Vasily; Evans, N Wyn; Deason, Alis J (Monthly Notices of the Royal Astronomical Society, 2019)
Using the data from the Sloan Digital Sky Survey and the Gaia satellite, we assemble a pure sample of ∼3000 Blue Horizontal Branch (BHB) stars with 7-D information, including positions, velocities and metallicities. We demonstrate that, as traced with BHBs, the Milky Way’s stellar halo is largely unmixed and can not be well represented with a conventional Gaussian velocity distribution. A single-component model fails because the inner portions of the halo are swamped with metal-rich tidal debris from an ancient, head-on collision, known as the “Gaia Sausage”. Motivated by the data, we build a flexible mixture model which allows us to track the evolution of the halo make-up across a wide range of radii. It is built from two components, one representing the radially anisotropic Sausage stars with their lobed velocity distribution, the other representing a more metal-poor and more isotropic component built up from minor mergers. We show that inside 25 kpc the “Sausage” contributes at least 50% of the Galactic halo. The fraction of “Sausage” stars diminishes sharply beyond 30 kpc, which is the long-established break radius of the classical stellar halo.
EPrint Processing Status: Full text deposited in DRO